Foaming characteristics of β-lactoglobulin as affected by enzymatic hydrolysis and polysaccharide addition: Relationships with the bulk and interfacial properties - Perez, Adrián Alejandro (2012)
The objective of this work was to study the effect of enzymatic hydrolysis and polysaccharide addition on the foaming characteristics of β-lactoglobulin (β-LG). Enzymatic treatment was performed in the hydrolysis degree (HD) range of 0.0–5.0% using bovine α-chymotrypsin II immobilized on agarose microbeads. Anionic non-surface active polysaccharides (PS), sodium alginate (SA) and λ-carrageenan (λ-C) were studied in the concentration range of 0.0–0.5 wt.%. Foaming characteristics were determined by conductimetric and optical methods and were linked to protein diffusion kinetics, film mechanical properties and biopolymer molecular dynamics in solution. Experiments were performed at constant temperature (20 °C), pH 7 and ionic strength 0.05 M. Limited hydrolysis improved the formation and stability of β-LG foam possibly due to an increased protein diffusion rate and film dilatational elasticity. Furthermore, PS addition caused different effects on β-LG foaming characteristics depending on the PS type, their relative concentration and extent of enzymatic treatment (HD). Diffusion rate and interfacial rheological behavior of mixed systems could exert a decisive role in foaming characteristics of β-LG and its hydrolysates in close connection with biopolymer interactions in solution, e.g., macromolecule repulsion, protein segregation/aggregation and soluble complexes formation.